(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: The purpose of this scholarly paper is to examine Walmart Inc.’s strategic evolution through the lens of artificial intelligence (AI) innovation, ethical considerations, and business transformation. By adopting an exploratory case study approach, the research seeks to analyze how Walmart integrates AI-driven solutions to enhance operational efficiency, customer experience, and competitive advantage while addressing ethical challenges. This study aims to contribute to the growing body of literature on corporate AI adoption, offering insights into sustainable and responsible innovation in the retail sector. Methodology: The research work contains an in-depth exploratory case study of Walmart Inc., analyzing its strategic evolution, technological innovation, and ethical commitments within the dynamic AI industry. By applying comprehensive business frameworks such as SWOC, ABCD, and PESTLE, the study aims to evaluate Walmart’s internal capabilities, external challenges, and societal responsibilities. The research further seeks to generate actionable insights that inform stakeholder engagement, competitive positioning, and the responsible development of AI in contemporary business environments. Analysis & Suggestions: The analysis of Walmart Inc. highlights its strong market presence, efficient supply chain, and growing integration of AI technologies to optimize operations and enhance customer experience. However, challenges such as ethical data use, workforce adaptation to automation, and competitive pressures from e-commerce rivals require strategic attention. It is suggested that Walmart strengthen its AI ethics governance, invest in employee reskilling programs, and diversify digital service offerings to sustain long-term competitiveness and social responsibility. Originality/Value: This study offers original insights by integrating strategic analysis frameworks with an AI-focused perspective to evaluate Walmart Inc.’s innovation, ethics, and business transformation. Unlike prior research that often examines retail performance in isolation, this paper uniquely connects Walmart’s technological advancements with its ethical responsibilities and competitive positioning. The findings provide valuable guidance for academics, industry leaders, and policymakers seeking to understand and replicate responsible AI adoption in large-scale retail operations. Type of Paper: Exploratory Case Study-Based Research.